2022
DOI: 10.1186/s13690-022-00958-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the spatial correlation and convergence of China's healthcare resources allocation: evidence from the Yangtze River Delta Region

Abstract: Background China’s imbalanced allocation of healthcare resources mainly arises from urban–rural and intercity differences, the solution of which has been the goal of reforms during the past decades. Estimating the spatial correlation and convergence could help to understand the impact of China’s fast-evolving medical market and the latest healthcare reforms. Methods The entropy weight method was used to construct a healthcare resource supply index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Most research has focused mainly on the spatial layout and accessibility of EMS facilities for optimal allocation (18)(19)(20)(21)(22)(23). Liu et al found that the equity of supply and demand for EMS resources is low based on data from death surveillance from 2008 to 2012 in Chongqing, China (24).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Most research has focused mainly on the spatial layout and accessibility of EMS facilities for optimal allocation (18)(19)(20)(21)(22)(23). Liu et al found that the equity of supply and demand for EMS resources is low based on data from death surveillance from 2008 to 2012 in Chongqing, China (24).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…This is in line with previous findings that China's healthcare reform has placed more emphasis on physical capital investment at the expense of human capital investment. 51 Since popular belief holds that significant differences exist between various county subsamples, we estimated the allocative efficiency of municipal districts and nonmunicipal counties separately and compared the means with the ANOVA method. Our findings show that nonmunicipal counties have a higher mean for different efficiency indicators than municipal districts.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous findings that China’s healthcare reform has placed more emphasis on physical capital investment at the expense of human capital investment. 51…”
Section: Discussionmentioning
confidence: 99%
“…By using the supply/demand index, we could reduce the dimensions of supply/demand indicators and better measure changes in supply and demand as shown in the existing literature. 39 The entropy weight method can determine the weight coefficients of different indicators based on the amount of information provided by observations, and it enables us to reduce the information lost in the calculation process. After standardizing the supply (input) and demand (output) indicators for each region i with equation (1) , we can calculate the supply index and demand index for each region i using the entropy weight method as follows:…”
Section: Methodsmentioning
confidence: 99%